Qualitative Research Synthesis: How the Whole Can Be Greater than the Sum of Its Parts. (1st June 2014) - Riese, Hanne; Carlsen, Benedicte; Glenton, Claire
Abstract : The rise of the knowledge society has led to an increase in the amount of research that is produced and an increased demand from decision makers for summaries of this research. As a result, research syntheses have become increasingly important in applied research, especially within the health sciences. However, this methodology has not been adopted with the same enthusiasm in the field of anthropology. In this article, we describe the main principles of this approach and the history of its development and discuss whether qualitative research synthesis can be seen as compatible with (the goal of) anthropological methodology. Finally, we argue for a greater adoption of research synthesis within applied anthropology and call for a greater engagement from anthropologists in the further development of this methodology.